FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI (SIA) PADA DINAS KESEHATAN PROVINSI BALI - I GUSTI AYU RATIH PERMATA DEWI; PUTU DIAH PUTRI IDAWATI (Forum Manajemen STIMI Handayani Denpasar, 2019)
This study aims to determine the factors that influence the performance of accounting information systems at the Bali Provincial Health Office. The data used are primary data in the form of questionnaires. Sample selection using saturated sampling method, namely the technique of determining the sample if all members of the population are used as a sample of 30 employees of the public section and staff of the Bali provincial health office. The test results show that User Involvement, HR Capability, Top Management Support affect the performance of the Accounting Information System (SIA).